Communication schedule optimization for foundation fieldbus H1 segment with dual cascade control loops - Sangsuwan, Thaksin; Pongswatd, Sawai; Julsereewong, Amphawan (My University, 2016)
This paper proposes a method for optimizing communication schedules of dual cascade control loops within the same Foundation Fieldbus (FF) H1 segment. Integrated Harmonas-DEO host system is utilized as a configuration tool for building control strategy and scheduling macrocycle of the studied H1 segment, which consists of two level-to-flow cascade control loops. Communication schedule optimization of two different cases of assigning control functions to run in the field devices is described. Method validation is based on the use of three metrics: latency improvement, publication gap improvement, and macrocycle utilization improvement. Comparison results between the natural macrocycle and optimized macrocycle show that the proposed method can improve not only the latency of control loop but also the availability of communication bandwidth.
Keywords: Cascade control; Communication schedule; Foundation fieldbus (FF); H1 segment; Macrocycle; Optimization